PERKEMBANGAN PERWAKAFAN DALAM PERUNDANG-UNDANGAN DI INDONESIA - Syarjaya, H.E Syibli (ALQALAM, 2009)
Ulama have agreed that the Islamic legal for waqf, as a social regulation, is sunna. However, since waqf deals with the public interest, the government is obliged to manage it in the law and regulation. Fiqh al-waqf in the law and regulation always develop from one period to the following ones in accordance with the evelopment of he Indonesian people's thought. This article hies to explore the development of waqf in Indonesian laws since the Dutch colonial period until 2006.